KOMUNIKASI SISWA BERKEBUTUHAN KHUSUS DI RUANG KELAS - Nurjaman, Enang Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
This study uses a qualitative approach to ethnography of communication, the purpose of this research was to (1). Explain the communicative situation or context of the communication of students with special needs in inclusive classrooms (2). explain communication events that occur in school classrooms inclusive, (3). explain the communicative acts contained in the behavior of children with special needs in inclusive classrooms. Informants were selected by purposive sampling. Data was obtained through depth interviews, participant observation, and document analysis. Supporting data were obtained from analysis of documents and interviews with relevant parties to the issue of inclusive schools and the education of students with special needs.